3D Fiber-Based Frame Element with Multiaxial Stress Interaction for RC Structures. (15th August 2018) - Kagermanov, Alexander; Ceresa, Paola
Abstract : A three-dimensional fiber-based frame element accounting for multiaxial stress conditions in reinforced concrete structures is presented. The element formulation relies on the classical Timoshenko beam theory combined with sectional fiber discretization and a triaxial constitutive model for reinforced concrete consisting of an orthotropic, smeared crack material model based on the fixed crack assumption. Torsional effects are included through the Saint-Venant theory of torsion, which accounts for out-of-plane displacements perpendicular to the cross section due to warping effects. The formulation was implemented into a force-based beam-column element and verified against monotonic and cyclic tests of reinforced concrete columns in biaxial bending, beams in combined flexure-torsion, and flexure-torsion-shear.